FALSAFAH KEPEMIMPINAN WALI SONGO DALAM PEMBENTUKKAN BUDAYA RELIGIUS DI LEMBAGA PENDIDIKAN ISLAM - Qurroti A’yun (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2020)
Abstract This article discusses the pattern of internalizing the value of leadership in forming a religious culture in Islamic educational institutions. Wali Songo Strong leadership often appears to be an alternative postmodern leadership style, as a leadership style that is wise and assertive but still down to earth as a leader. This article aims to review leadership styles, one of which is the Wali Songo leadership style. This article's method uses a literature study, and the author looks for sources from journals, books, and other supporting sources. The Wali Songo leadership style in a school principal can be a measure of the leadership of the Islamic culture in the school's scope. Keywords: leadership, wali songo, religius cultural.